The Penguin dictionary of curious and interesting numbers - Wells, D. G. (David G.) (London, England ; Penguin Books, 1997)
Contains numerically arranged entries that provide information about some of the more interesting properties of numbers and how they work.
Spine title: Curious and interesting numbers.
Includes bibliographical references (page xix-[xx]) and index.
Adult
Adult
Keywords: Number theory; Number theory